The Supermajority Coalition and the Legal Policy of the 2025 National Legislation Program Challenges - Irmanjaya Thaher; Rita Alfiana (Hakamain: Journal of Sharia and Law Studies, 2024)
This article examines Indonesia’s national legal policy for the 2024–2025 period, focusing on the legislative priorities of the Prabowo–Gibran administration under the Red-White Cabinet, supported by the Indonesia Maju Coalition (KIM) Plus. The study analyzes the 2025 Priority National Legislation Program (Prolegnas), consisting of 42 bills, including 33 proposed by the House of Representatives (DPR), 8 by the government, and 1 by the Regional Representatives Council (DPD). It also examines the 2024–2029 Medium-Term National Legislation Program, in which 45% of bills remain at the drafting stage, 28% are undergoing first-level deliberation, 21% are new proposals, and 6% are in harmonization. The article investigates legislative dynamics within the context of the DPR’s supermajority coalition and evaluates the implications of KIM Plus’s political dominance for legislative quality, institutional checks and balances, and democratic accountability. It further explores the Prabowo–Gibran “Asta Cita” agenda as the ideological framework guiding legislative priorities and assesses its influence on legal reform and national governance. Finally, the study identifies key challenges in maintaining transparent, participatory, and evidence-based lawmaking while proposing recommendations to strengthen an inclusive, responsive, and accountable national legal policy that balances political stability with democratic representation, constitutional principles, and the broader public interest.